2019
DOI: 10.2147/cia.s197982
|View full text |Cite
|
Sign up to set email alerts
|

<p>Reticulocyte levels have an ambivalent association with hypertension and atherosclerosis in the elderly: a cross-sectional study</p>

Abstract: Purpose: Age-related reduction in bone marrow activity has been shown to cause anemia, and hypertension and endothelial dysfunction (atherosclerosis) are age-related diseases. However, recent studies have revealed a close association between bone marrow activity and endothelial maintenance. This study aimed to determine the association between elevated reticulocyte levels in conjunction with vigorous bone marrow activity and hypertension and atherosclerosis among the elderly. Study popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 37 publications
3
15
0
Order By: Relevance
“…In a previous study, were found that the MAF of rs3782886 (BRAP) was significantly positively associated with a high platelet count, which is associated with hypertension 16 , supports this mechanism. In addition, as in our previous study 15 , here, we found a significantly positive association between reticulocyte levels and hypertension (Table 2, Fig. 1b), while no significant association was found between reticulocyte levels and genetic factors (rs3782886 and rs671) (Tables 3, 4, Fig.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In a previous study, were found that the MAF of rs3782886 (BRAP) was significantly positively associated with a high platelet count, which is associated with hypertension 16 , supports this mechanism. In addition, as in our previous study 15 , here, we found a significantly positive association between reticulocyte levels and hypertension (Table 2, Fig. 1b), while no significant association was found between reticulocyte levels and genetic factors (rs3782886 and rs671) (Tables 3, 4, Fig.…”
Section: Discussionsupporting
confidence: 90%
“…And reticulocyte is revealed to be significantly positively associated with hypertension ( Table 2, Fig. 1b) as like previous our study 15 . Since hypertension injures endothelium strongly, lower levels of reticulocytes among the elderly indicate a lower capacity for vascular maintenance.…”
Section: Discussionsupporting
confidence: 88%
“…Factors such as alcohol consumption and smoking status influence vascular remodeling. Alcohol consumption influences γ-GTP and smoking status influences WBC [ 22 ]; therefore, we included γ-GTP and WBC as confounding factors rather than considering these factors directly, as in a previous study [ 6 , 13 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Hypertension is known to be strongly associated with atherosclerosis [ 5 , 6 ]. Previously, we reported that active endothelial repair, which results in atherosclerosis, might have a beneficial influence on maintaining muscle strength among hypertensive older Japanese [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Long-term elevated blood pressure causes and promotes the formation and development of atherosclerosis. Immune and inflammation run through the whole process of the occurrence and development of atherosclerosis, of which, inflammation may be a bridge connecting hypertension and atherosclerosis, [ 17 , 18 ] and inflammation is an important participant on the mechanism of hypertension in atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%